Seller ethnicity and property characteristics: foreclosure sales in Malaysia - Wong, Woei Chyuan; Lee, Janice Yim Mei; Daud, Md Nasir; Ng, Pooi Leng (Emerald, 2017)
Purpose: The purpose of this paper is to examine the determinants of property sale probability and sale price at auction in Kuala Lumpur, Malaysia. Design/methodology/approach: A two-stage Heckman sample selection model is used for this research. The first stage involves the estimation of a probit model on a successful sale. The second stage introduces an additional selection variable, the inverse Mills ratio, as an explanatory variable to the sale price estimation equation. Findings: The authors find that Chinese-owned auctioned properties have higher sale probability and are sold at higher prices as compared to Indian and Malay-auctioned properties. Properties auctioned by the largest auction house outperformed other smaller auctioneers. Auction characteristics such as proximity to the city center, number of previous auction attempts and number of online viewers are positively related to sale price and sale probability. Social implications: The findings on the substantially lower sale price obtained by Malay and Indian borrowers compared to their Chinese counterparts imply that it is much harder for these borrowers to be relieved from financial distress. The two plausible explanations offered in this paper for this price differential, i.e. racial residential segregation and ownership restriction, warrant further study. Originality/value: First, the authors consider the explanatory power of seller ethnicity, number of online viewers and auctioning route which are new to the literature. Second, they use a Heckman model that addresses possible selection bias of sold properties. This methodology is unexplored in the auction literature.